الطاقات المتجددة ودورها في حماية البيئة والتنمية الاقتصاديةفي الجزائر - ماني نوال (المسيلة, 2023)
إن الطاقة تعد أحد المحركات الأساسية للاقتصاد العالمي، وهي العنصر الأهم الذي يعتمد عليه أي تطور، إلا أنه ونتيجة للتقدم التقني والعلمي المتزايد تزايد الطلب على المصادر المختلفة للطاقة، وانعكس ذلك على مواردها، من خلال الاستهلاك المفرط والغير عقلاني لمصادر الطاقة الأحفورية، لذلك أصبح الكل يعي جيدا أن هذه المصادر المعتمد عليها حاليا بشكل واسع ستصل إلى قمة إنتاجها، مما طرح مشكلة استنفادها وتسبب في تذبذب أسعارها في الأسواق الدولية، كما رافق ذلك ظهور العديد من المشاكل والضغوطات البيئية، من التلوث البيئي إلى الاحتباس الحراري وصول إلى التغيرات المناخية وغيرها، التي تعد من أبرز المشاكل المعاصرة التي تواجه الإنسان والبيئة وتسهم في الحد من التطور الاقتصادي والاجتماعي في العالم. لذلك ارتفعت أصوات عديدة في العقود الأخيرة تطالب بالحفاظ على البيئة، وتدعو للبحث عن البدائل التي يمكن الاعتماد عليها في المستقبل. ومن بين أهم الموارد الطبيعية التي أصبحت تشكل جدوى وأهمية قصوى سواء لتحقيق التنمية الاقتصادية المستدامة أو حماية البيئة، هي الطاقات المتجددة التي تعتبر أحد أهم البدائل المتاحة، إذ تشكل إمداداتها عاملا أساسيا في دفع عجلة الإنتاج وتحقيق الاستقرار والنمو، مما توفر فرص العمل الدائمة وتسهم في تحسين مستويات المعيشة والحد من الفقر عبر العالم. فضال عن كونها تعتبر الطاقة الصديقة والنظيفة للبيئة، فهي تحمل في طياتها تحقيق التوازن البيئي والنمو المستدام وتأمين الطاقة للأجيال الحالية والمستقبلية. وتوصلت الدراسة بذلك، إلى أنه للطاقة المتجددة القدرة على تلبية حاجة التطور في البلدان المتقدمة والنامية على حد سواء، فضال عن قدرتها على زيادة التطور والنمو على نطاق واسع، إذ تعد موارد الطاقة المتجددة وتقنياتها عنصرا أساسيا من عناصر التنمية الاقتصادية المستدامة، وتوصلت الدراسة كذلك إلى أن الأضرار البيئية الناتجة عن استعمال مصادر الطاقات المتجددة أقل من مثيلاتها من المصادر الطاقوية الأخرى، ويمكن أن توفر إمدادات مستدامة يمكن الاعتماد عليها، حيث أنها متوفرة أوال وكونها مصادر طبيعية ال تنفد كالشمس والرياح ثانيا. كما توصلت الدراسة إلى أن الجزائر تمتلك من الامكانيات ما يؤهلها إلى أن تكون من الدول الرائدة عالميا وليس فقط إقليميا في مجال الطاقة المتجددة، وذلك إذا اتبعت سياسات ناجعة أكثر من أجل تحقيق هذا الهدف والقيام بالتطبيق الفعلي لها.   Resume : Energyis one of the fundamentalpillars of the global economy and one of the most important elements in all developmentprocesses. However, scientific and technologicalprogress has caused an increase in the demand for differentenergy sources. This demand has led to excessive and irrationalconsumption of fossil fuels in general. Economic agents (and States, in particular) have thusbecomeaware that the production of energyresources (fossils, in particular) willsoonreach a maximum. This canonlygeneratesomeconcern about the depletion of theseresources and the erraticpricemovements that this situation will cause. In addition, the use of fossilenergy sources causes manyenvironmentalproblems, such as pollution, greenhouseeffects and climate change in general, which are among the major challenges facinghumanity and the environment. environment are faced. Theseconsequences of the use of fossilenergy sources alsocontribute to the regression of social and economicdevelopment in the world. During the last decades, calls for the preservation of the environment have becomerecurrent and aim first and foremost to put in place reliable alternatives for the future. Renewableenergyis one of the energy sources that canplay an important role in achieving and protectingsustainabledevelopment and the environment. They are generallyconsidered as alternative and available solutions and their almostunlimitedreservesconstitute a certain guarantee in terms of growth and development, the latter creatingadditionalemploymentopportunities and improving the standard of living of the populations, in general. Theseso-called clean and environmentallyfriendlyenergiesaim to maintain a balancedenvironment, sustainabledevelopment and to ensureenergy sources for present and future generations. The lessonsdrawnfromthis study suggest that renewableenergies are able to meet the requirements of the economicevolution of developed countries and those of developing countries. They (renewableenergies) are also capable of accelerating the pace of development in these countries sincetheseenergy sources and the technicalmeansattached to them are fundamentalelements of sustainabledevelopment. The study goes on to point out that the environmental damage caused by other types of energy sources is more perniciousthan that which wouldbecaused by the widespread use of renewableenergy sources, the latter (solar and wind power, for example) that canensure an almostunlimitedsupply of energy. Algeria has all the capabilities to become a leading country in the field of renewableenergies if an energypolicyisclearly set in motion
Keywords: الطاقات المتجددة - حماية البيئة - التنمية الاقتصادية - الجزائر